Characteristics of Mining-Induced Fractures Under Inclined Coal Seam Group Multiple Mining and Implications for Gas Migration - Ran, Qican; Liang, Yunpei; Zou, Quanle; Zhang, Bichuan; Li, Rifu; Chen, Zihan; Ma, Tengfei; Kong, Fanjie; Liu, Han (Natural resources research (New York, N.Y.), 2023)
The accurate identification of gas migration channels and enrichment regions is essential for the utilization of gas resources and safe coal mine production, which are closely related to the evolution of mining-induced fractures. Therefore, we conducted a similarity simulation study of inclined coal seam group multiple mining, adopting the 1930 Coal Mine in Xinjiang, China, as the subject. First, the evolution of mining-induced fracture parameters was elucidated. Then, the gas migration and enrichment characteristics under inclined coal seam group multiple mining were investigated. Finally, a surface well gas extraction test was performed in the mining area to verify the experimental results. The results showed that under inclined coal seam group multiple mining, the frequency, angle and width of mining-induced fractures exhibited significant asymmetric characteristics. Additionally, the surface area percentage and fractal dimension of mining-induced fractures indicated a trend of an initial large increase followed by a small increase. Moreover, under inclined coal seam group multiple mining, mining-induced fractures were more developed in the right fracture area, and gas was smoothly transported, resulting in a more likely gas enrichment region. Based on the characteristics of mining-induced fracture parameters, a step-by-step method for determining gas migration channels and enrichment regions was proposed. Moreover, the surface well gas extraction test in the mining area revealed satisfactory extraction effects. This research aimed to increase the amount of gas extraction and to achieve safe mining of inclined coal seam groups.